Sex differences in overweight and obesity among Mexican Americans in the National Health and Nutrition Examination Survey: A comparison of measures. (December 2022) - Gough Courtney, Margaret; Carroll, Alyssa
Abstract: The increasing prevalence of overweight and obesity in the United States, and disparities by race, ethnicity, and gender, have caused concern among public health practitioners, health care providers, and others, in part because overweight and obesity may be linked to chronic health problems and weight stigma. Researchers have traditionally relied upon body mass index (BMI) as a measure of overweight and obesity, despite its limitations. In this study we apply an intersectional framework and use data from the 2011–2018 waves of the nationally representative National Health and Nutrition Examination Survey (NHANES) to study sex differences in the risk of overweight and obesity among Mexican Americans, triangulating three measures that proxy for overweight and obesity: BMI, high waist circumference, and high percent body fat. We assess heterogeneity across nativity, education, income by parenthood status, food security, time in the United States (for immigrants), and receipt of SNAP/WIC benefits (for the low-income sample). Results from logistic regression models indicate choice of cutoff values and measure are critical to determining whether sex disparities exist. We find no evidence of disparities in BMI but evidence of greater risk for females using traditional cutoff values for high waist circumference and high percent body fat. Adjusted cutoff values provide differing results. Minimal heterogeneity is seen. Results reinforce the importance of considering sex disparities and emphasize the importance of critically examining measures that proxy for overweight and obesity risk, given the high stakes surrounding weight stigma. Highlights: Race/ethnic and gender differences in overweight/obesity are a concern in the U.S. Overweight and obesity are typically measured using body mass index Using multiple measures and cutoffs of overweight and obesity is valuable Different measures and cutoffs change evidence for sex disparities